2011
DOI: 10.1586/eri.11.44
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy and HIV coinfection: a critical approach

Abstract: An increase in leprosy among HIV patients, similar to that observed in patients with TB, was expected approximately 20 years ago. Studies conducted in the 1990s together with those reported recently seemed to indicate that a coinfection with HIV did not alter the incidence and the clinical spectrum of leprosy and that each disease progressed as a single infection. By contrast, in countries with a high seroprevalence of HIV, TB was noted to increase. Explanations may be provided by the differences in the incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…It is stated that cellular immunity towards Mycobacterium leprae infection remains intact in spite of the low CD4 count. 15 One patient developed type 1 reaction within six months of starting HAART and we believe this to be a manifestation of IRIS following HAART which has been described earlier. 16 The most commonly observed viral infection among the HIV patients was herpes zoster which is in accordance with certain previous studies.…”
Section: Discussionsupporting
confidence: 64%
“…It is stated that cellular immunity towards Mycobacterium leprae infection remains intact in spite of the low CD4 count. 15 One patient developed type 1 reaction within six months of starting HAART and we believe this to be a manifestation of IRIS following HAART which has been described earlier. 16 The most commonly observed viral infection among the HIV patients was herpes zoster which is in accordance with certain previous studies.…”
Section: Discussionsupporting
confidence: 64%
“…Considering the same IRIS criteria previously used by our group to define IRIS cases [13], 93 out of 9 IRIS/RR patients (Hs012, Hs024 and Hs043) can be really defined as IRIS cases, since they developed the symptoms during the first 6 months of HAART . However, others studies also identified IRIS cases at periods of longer than 10 months [30]. In this study, we aimed to characterize some of the key T cell phenotypes involved in the HIV/leprosy interaction in coinfected vs. non-coinfected patients and analyze some major features of the IRIS/RR phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to current WHO views, which state that there is no association between leprosy and HIV. Immune reconstitution inflammatory syndrome (IRIS) has been reported where leprosy has been unmasked in patients on antiretroviral treatment (Massone et al. 2011; Rao et al.…”
Section: Discussionmentioning
confidence: 99%